Implementation of The Islamicity Performance Index Approach to Analysis of Sharia Banking Financial Performance In Indonesia - Naning Fatmawatie (Fakultas Ekonomi, UIN Maliki Malang, 2021)
Islamic bank performance appraisal uses criteria with specific characteristics, namely the Islamicity Performance Index. This study aims to analyze the development of the financial performance of Islamic Commercial Banks in Indonesia. This type of research is descriptive quantitative research. Sampling using purposive sampling. The analysis technique uses non-statistical quantitative methods. This study indicates that the PSR tends to increase, and the best is Bank Mega Syariah. The best ZPR of BNI Syariah. BRI Syariah's best EDR Qard, for the best EDR Employees Bank Mega Syariah, for the best EDR Dividend BSM. BSM's best EDR net profit. For WD-Employee, Mega Syariah Bank's best ratios and for income syariah VS Non income syariah are all very good. This research implies that it can contribute to Islamic Commercial Banks to evaluate their performance primarily for the Zakat Performance Ratio so that the role of Islamic social banks will be better.